Individual lives in collectivist faces : On social norms in a radio show - Anchimbe, Eric (Research Developments in World Englishes, 2021)
African (postcolonial) societies function as collectivist group-based cultures. The worth of the individual is often measured in terms of the worth of their group. The individual, therefore, prioritises the defence and preservation of the group’s face even above theirs. Using data collected from an out-of-studio radio programme in Cameroon, I demonstrate how individual lives and faces are often subsumed into the group’s face in these interactions that take place in the public sphere. Relying on the postcolonial pragmatics framework, I analyse this specific Cameroon English discourse for markers of collectivist group values and social norms, and for how interlocutors factor these into their social interactions. They adopt and perform asymmetrical kinship, social affective roles and tasks, give and take advice, and reproach and accept blame in line with societal norms built on interlocutors’ age, social status, social hierarchy and sometimes gender. Performing these potentially (individual) degrading acts in public shows how strong allegiance is to the collectivist group, its culture and norms.